Flexural Behavior of Slurry Infiltrated Waste Plastic Fiber Concrete - Ali, Dheyaa; Al-Hadithi, Abdulkader; Farhan, Ahmed (Iraqi Journal of Civil Engineering, 2023)
Slurry infiltrated fiber concrete (SIFCON) is a relatively new high performance material and can be considered a special type of fiber concrete (FRC) with high fiber content. The matrix consists of a flowing mortar or cement slurry that must penetrate well through the network of fibers placed in the mold. SIFCON has excellent mechanical properties combined with high ductility and toughness values. SIFCON a relatively new material, is composed of mud (cement or cement and sand), water, a plasticizer (water reducer), and fibers. All previous studies have used waste steel fibers, steel fibers and other fibers, but in this study, plastic fibers were made from polyethylene terephthalate (PET) by cutting carbonated beverage bottles. The main objectives of this study are: Determination the effect of the waste plastic fiber volume ratio on the strength and deformation of (SIFCON) samples under the influence of bending loads. Both flexural strength and toughness properties were determined by testing samples (100×100×400) mm at 28 and 56 days of age. The results obtained from these tests were compared with those performed on conventional tests. Aspect Ratio equal to (36.8) and three volume ratios (3%, 5% and 7%) of the total volume of the concrete mixture were used to add fibers with different volume ratios. A conventional concrete mix was created as a reference for comparison. Bending strength and fresh concrete tests were performed. And compared with the reference mixture and according to the analysis of the results. The results showed an improvement in bending strength .It was found through the flexural examination that the flexural strength of the mixture containing fiber percentage (7%) achieved the highest strength compared to the rest of the ratios used, compared with the reference mixture (Ref.) by (32.25, 27.5)% for ages (28, 56), respectively.